2016
DOI: 10.1002/admi.201600811
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Current Collector on Performance of Li‐S Batteries

Abstract: Efficient, scalable energy storage systems such as lithium‐sulfur batteries have become a technological bottleneck for the growing energy demands in automotive sector. To realize the ultimate performance of such batteries, the effect of all structural components of the batteries has to be considered. Nowadays the effect of current collectors appears to be less explored in the battery research field. Therefore, this report draws attention to exploit different current collectors such as, copper, aluminum, platin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Regarding the metal used as a current collector material, Raguzin et al found aluminum and platinum foils to be inert towards the electrochemical reactions in Li-S batteries with sulfur/carbon black cathode materials obtained by melt diffusion. 370 However, in the voltage range of 1.0-3.0 V, nickel foil is electrochemically active (Ni (0) / Ni (I/II) 3 S 2 / Ni (II) S) and contributes to the measured capacity resulting in etching and therefore a lower cycling stability and a voltage drop for nickel current collectors. Consequently, aer 30 cycles, the assembled cell predominantly behaves as a Ni 3 S 2 /Li battery supplying a voltage of 1.4 V. Earlier studies on nickel foam current collectors also indicated the involvement of Ni in the electrochemical conversion reaction observing NiS on the foam surface aer several cycles when discharged below 1.5 V. 371,372 The effect of side reactions with nickel can be minimized by adding Si or SiO 2 as dopants or narrowing the cut off voltage.…”
Section: The Role Of Metal Current Collectors In the Positive Electrodementioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the metal used as a current collector material, Raguzin et al found aluminum and platinum foils to be inert towards the electrochemical reactions in Li-S batteries with sulfur/carbon black cathode materials obtained by melt diffusion. 370 However, in the voltage range of 1.0-3.0 V, nickel foil is electrochemically active (Ni (0) / Ni (I/II) 3 S 2 / Ni (II) S) and contributes to the measured capacity resulting in etching and therefore a lower cycling stability and a voltage drop for nickel current collectors. Consequently, aer 30 cycles, the assembled cell predominantly behaves as a Ni 3 S 2 /Li battery supplying a voltage of 1.4 V. Earlier studies on nickel foam current collectors also indicated the involvement of Ni in the electrochemical conversion reaction observing NiS on the foam surface aer several cycles when discharged below 1.5 V. 371,372 The effect of side reactions with nickel can be minimized by adding Si or SiO 2 as dopants or narrowing the cut off voltage.…”
Section: The Role Of Metal Current Collectors In the Positive Electrodementioning
confidence: 99%
“…Consequently, aer 30 cycles, the assembled cell predominantly behaves as a Ni 3 S 2 /Li battery supplying a voltage of 1.4 V. Earlier studies on nickel foam current collectors also indicated the involvement of Ni in the electrochemical conversion reaction observing NiS on the foam surface aer several cycles when discharged below 1.5 V. 371,372 The effect of side reactions with nickel can be minimized by adding Si or SiO 2 as dopants or narrowing the cut off voltage. 370 Zhao et al potentiostatically electrodeposited sulfur nanodots from a 0.1 M Na 2 S aqueous solution on a nickel foam and then applied the obtained composite as a positive electrode in Li-S batteries. 357 Such devices achieved a reversible capacity of 775 mA h g À1 aer 200 cycles at 0.5C in the smaller voltage range of 1.7-2.6 V for a comparably low sulfur loading of 0.84 mg cm À2 .…”
Section: The Role Of Metal Current Collectors In the Positive Electrodementioning
confidence: 99%
“…All the contact interfaces with polarized Cu (Cu x + ) are expected to immobilize the produced polysulfides (S n 2– ) and reduce their dissolution in electrolyte during charge/discharge processes (Figure e). In contrast, the interface between the Al foil surface and S is inactive, and the shuttle effect of S n 2– is extremely serious during cycling, as shown in Figure f . Consequently, S electrodes (S nanosheets or S partcies) with Cu substrates exhibit high electroactivity compared with Al substrate.…”
mentioning
confidence: 99%
“…The peaks at 642.4 and 641 eV are assigned to the Mn 4+ and Mn 2+ of MnO 2 , and the two satellite peaks are located at 643.6 and 645.2 eV Figure e exhibits the O 1s spectrum, in which the main peaks at 529.7, 531.4, and 533.2 eV are attributed to the Mn–O (latt), Mn–OH, and CO 2 , respectively . In Figure d, the high-resolution XPS spectrum of the S 2p peak could be deconvoluted into four peaks at 164.8 and 163.6 eV and 169.7 and 168.3 eV, which were ascribed to the elemental sulfur and SO x species, respectively.…”
Section: Results and Disscussionmentioning
confidence: 96%
“…52 Figure 3e exhibits the O 1s spectrum, in which the main peaks at 529.7, 531.4, and 533.2 eV are attributed to the Mn−O (latt), Mn−OH, and CO 2 , respectively. 53 In Figure 3d, the highresolution XPS spectrum of the S 2p peak could be deconvoluted into four peaks at 164.8 and 163.6 eV and 169.7 and 168.3 eV, which were ascribed to the elemental sulfur and SO x species, respectively. Importantly, the SO x species was derived from the strong S−O reciprocities between sulfur and MnO 2 , which had a "polythionate mechanism" to accelerate the conversion of LPSs.…”
Section: Results and Disscussionmentioning
confidence: 99%